Impacts of summer-seeded legume cover crops and termination-tillage method on nitrogen availability to corn in rotation - Yang, Xueming; Reynolds, W. Daniel; Drury, Craig F.; Reeb, Mary-Anne (Frontiers in Soil Science, 2023)
Summer-seeding legume cover crops can reduce erosion, mitigate nitrate leaching losses during the non-growing season, and provide bio-accumulated nitrogen (N) to the following crop. Very little information is available, however, on the most effective methods for terminating summer-seeded cover crops, or on the amount of N they can provide to subsequent crops. We therefore evaluated the impacts of selected legume cover crops and cover crop termination-tillage methods on corn (Zea mays L.) N credit and grain yield in a soybean (Glycine max Merr.) - winter wheat (Triticum aestivum L.) / cover crop - corn rotation over 3 consecutive years on a clay loam soil in southwestern Ontario. The cover crops were summer-seeded after wheat harvest, and included hairy vetch (Vicia villosa L. Roth), red clover (Trifolium pratense L.), white clover plus crimson clover mix (incarnatum and Trifolium alba L.), and a no cover crop control (CK). The cover crops were nested within termination-tillage method, including moldboard plow-down in fall, and herbicide spray-down in spring under strip-tillage or no-tillage then corn planting. Nitrogen fertilizer to corn was applied via side-dress at 200 kg N ha-1 to the CKs, and at 100 kg N ha-1 to the cover crops. Averaged over 3 years, above-ground biomass N level followed the pattern: hairy vetch > white clover plus crimson clover mix > red clover for fall plow-down termination. There were no significant differences in cover crop biomass N levels for spring termination. Corn response to cover crop was significantly affected by termination-tillage method and cover crop species, with poor corn stands after no-tillage, red clover and white plus crimson clover. Fall plow-down termination provided a range in N credit of 80-85 kg N ha-1, which was significantly greater than the N credit under herbicide spray-down in spring. Under spring strip-tillage and no-tillage, hairy vetch produced significantly greater corn grain yields than white plus crimson clover mix.